High phenotypic variability in Gerstmann-Sträussler-Scheinker disease - Smid, Jerusa; Studart, Adalberto, Neto; Landemberger, Michele Christine; Machado, Cleiton Fagundes; Nóbrega, Paulo Ribeiro; Canedo, Nathalie Henriques Silva; Schultz, Rodrigo Rizek; Naslavsky, Michel Satya; Rosemberg, Sérgio; Kok, Fernando; Chimelli, Leila; Martins, Vilma Regina; Nitrini, Ricardo (Arquivos de Neuro-Psiquiatria, 2017)
Gerstmann-Sträussler-Scheinker is a genetic prion disease and the most common mutation is p.Pro102Leu. We report clinical, molecular and neuropathological data of seven individuals, belonging to two unrelated Brazilian kindreds, carrying the p.Pro102Leu. Marked differences among patients were observed regarding age at onset, disease duration and clinical presentation. In the first kindred, two patients had rapidly progressive dementia and three exhibited predominantly ataxic phenotypes with variable ages of onset and disease duration. In this family, age at disease onset in the mother and daughter differed by 39 years. In the second kindred, different phenotypes were also reported and earlier ages of onset were associated with 129 heterozygosis. No differences were associated with apoE genotype. In these kindreds, the codon 129 polymorphism could not explain the clinical variability and 129 heterozygosis was associated with earlier disease onset. Neuropathological examination in two patients confirmed the presence of typical plaques and PrPsc immunopositivity.
Keywords: Gerstmann-Sträussler-Scheinker disease; prion diseases; prions